Multilingualism in Spain : sociolinguistic and psycholinguistic aspects of linguistic minority groups - Turell, M. Teresa, 1949- (Multilingual matters (Series), 2001)
Multilingualism in Spain deals with the sociolinguistic and psycholinguistic aspects of established and new migrant minority groups in Spain. Three guiding analytical research approaches cut across minorities in Spain: language, migration and discrimination, although not all aspects apply to all minorities in the same way: some are characterised by language, migration and discrimination; other communities are only defined by language and migration, but their members are not discriminated against socially and culturally; another group of communities are not characterised by recent migration, but they are discriminated against and/or their languages not even officially recognised; lastly, there are some other communities that do not find enough legal and institutional support and their languages may suffer discrimination.